Träning av motorisk/postural kontroll - Abrahamsson, Sofia (2014)
Humans and dogs are both mammals. One of the differences between the two species is that man walk on two legs and dogs on four legs. There are also differences in the nerve system between the two species. The human nerve system is supposed to provide opportunity for fine motor tasks- while the nerve system of the dog is more focused on the ability to perform locomotor tasks. Humans need to increase their motor control and postural control when affected by various conditions and diseases. Therefore, we have created theories and researched how this can be accomplished. Dogs are also affected by disease and similar conditions. But less is known about what treatment they need and what needs to be treated.